Pelatihan Pembuatan Egg Tofu dalam Inovasi Membuat Makanan Praktis di PKK Kelurahan Mangunsari Gunugpati Semarang - Erwin Nofiyanto; Sudjatinah; Sri Budi Wahjuningsih (JPM: Jurnal Pengabdian Masyarakat, 2023)
Mangunsari Village is a Village located in Gunungpati District, Semarang City. Most of the women from the PKK group in Mangunsari, Gunungpati, Semarang, mostly work as farmers and factory workers during the day. There needs to be an increase in the skills of the women of the PKK Group, Mangunsari Gunungpati Village, Semarang, one of which is the skill of making egg tofu. Egg Tofu is one of the processed tofu products made from soybean extract and chicken eggs which has a high nutritional content. Making egg tofu besides using soy milk is mixed with eggs, using an optimal percentage of eggs is needed to produce good quality egg tofu products. The addition of a high percentage of eggs can increase the nutritional value of egg tofu. Training Provision of skills in making Egg Tofu can increase knowledge of new business analysis which can increase family income. Partners before the implementation of the service answered 77.27% did not know, understand and had never made egg tofu, on the contrary 27.73% who answered had eaten egg tofu, whereas after carrying out this activity the PKK group mothers answered 100% had liked, understood and knew how to make egg tofu. The egg tofu making training is expected to inspire parents to innovate in making practical, easy to make, attractive food and can be a business opportunity that can increase family income.